2022
DOI: 10.1038/s41531-022-00403-x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of brain morphometry related to deep brain stimulation outcome in Parkinson’s disease

Abstract: While the efficacy of deep brain stimulation (DBS) is well-established in Parkinson’s Disease (PD), the benefit of DBS varies across patients. Using imaging features for outcome prediction offers potential in improving effectiveness, whereas the value of presurgical brain morphometry, derived from the routinely used imaging modality in surgical planning, remains under-explored. This review provides a comprehensive investigation of links between DBS outcomes and brain morphometry features in PD. We systematical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 79 publications
0
1
0
Order By: Relevance
“…Decreased brain volume and increased electrode displacement were associated with reduced motor improvements following STN-DBS. The brain atrophy results were consistent with previous studies, which found that the ventricular volume and atrophy of the motor cortex and thalamus were associated with poor motor improvement after DBS [34,35]. In terms of electrode displacement, Choi et al [36] analyzed the impact of brain shift on subcallosal cingulate DBS and found that electrode displacement decreased the connectivity between the electrode and ventral striatum.…”
Section: Impact Of Electrode Displacement On Stn-dbs Efficacysupporting
confidence: 87%
“…Decreased brain volume and increased electrode displacement were associated with reduced motor improvements following STN-DBS. The brain atrophy results were consistent with previous studies, which found that the ventricular volume and atrophy of the motor cortex and thalamus were associated with poor motor improvement after DBS [34,35]. In terms of electrode displacement, Choi et al [36] analyzed the impact of brain shift on subcallosal cingulate DBS and found that electrode displacement decreased the connectivity between the electrode and ventral striatum.…”
Section: Impact Of Electrode Displacement On Stn-dbs Efficacysupporting
confidence: 87%
“…High beta and gamma cortical synchronization were shown to be increased by DBS as evaluated by MEG, especially in the motor, occipitoparietal, temporal, and prefrontal regions. This was discussed as non-normalizing functional connectivity caused by DBS 34 . The low gamma band displays the whole brain increases in DBS ON.…”
Section: 6 the Dbs On Connectivity Patterns And Cognitionmentioning
confidence: 99%
“…4,5 Their widespread clinical application, however, is limited by the need for additional and sometimes time-consuming scanning protocols and the expertise to analyse and translate their results. 6 Therefore, the association of postoperative outcomes with metrics based on T1weighted sequences obtained in clinical routine during surgical planning has been investigated. Particularly, analyses focussing on morphometric tissue features, such as voxelbased morphometry (VBM), have lately received increasing attention to monitor clinical progression and treatment effects.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, analyses focussing on morphometric tissue features, such as voxelbased morphometry (VBM), have lately received increasing attention to monitor clinical progression and treatment effects. 6 In a recent meta-analysis including 1253 patients enrolled in 24 studies, Wang and colleagues identified specific areas whose morphometric features were associated with outcomes following STN-DBS. 6 Here, atrophy of the motor cortex and thalamus was associated with below-average improvement in motor symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation